CODESRIA Bulletin Online, No. 10, December 2023 - The Commitment of the Pan-African Intellectual* - Shivji, IssaG. (CODESRIA Bulletin, 2023)
* Keynote Address to the Inaugural Conference of the African Humanities Association, Cape Town, 27-29 November 2023. Intellectual? What Intellectual? Intellectual, what intellectual? I am not given to definitions. I believe concepts are historical and social constructs responding to and reflecting the social conditions of the time. Yet human history is not divided by a Chinese wall. Just as the past weaves into the present, so concepts of the past are assimilated in the present. Half a century ago, when I was a law undergraduate at the University College Dar es Salaam, we were fired by Paul Baran’s essay ‘The Commitment of the Intellectual’. That essay still resonates with me. We were the first post-Arusha Declaration generation at the university. The ruling party, TANU (Tanganyika African National Union), under Nyerere, had just announced its policy on socialism and self-reliance. The Campus or the Hill, as we fondly called it, was awash with debates on the role of the national university in a country aspiring to build socialism. Having just emerged from the ‘traumatic’ experience of the expulsion of some 393 students in October 1966,[1] the faculty struggled to redeem itself by revisiting their teaching and learning methods. The faculty was prepared to experiment with innovative pedagogy to inculcate in their students a sense of social commitment and critical enquiry. The intellectual space was prised open. Hegemonic bourgeois ideas and liberal values were challenged. Nothing was sacred. Concepts were questioned, interrogated, discarded. In some cases, dogmatic students on the fringes of the radical core even ridiculed and demonised the holders of such ideas. This was all part of the struggle. We were waging what we perceived to be an ideological struggle. In these conditions the concept of the committed intellectual came under scrutiny. Who is an intellectual? What constitutes their commitment? A second-year undergrad wrote an essay titled ‘The Educated Barbarians’ in the inaugural issue of the radical student’s magazine, Cheche, named after Lenin’s Iskra and Nkrumah’s The Spark. He condemned his fellow students for indulging in frivolities and failing to ask the bigger questions, instead pleading professional objectivity and the scientific, and therefore apolitical, nature of their specialisations. Replete with quotations from Baran, the essay ended with a conclusion that echoed what was then considered intellectual commitment. So comrades, let us not deceive ourselves. Intellectual stagnancy, ignorance, apathy and attitudes of non-commitment and indifference are as great an enemy on the campus as are poverty, ignorance and disease in the country—for from both of these it is imperialists and exploiters who benefit and the masses who suffer. Let us not be complacent. If we think we are educated, we had better re-examine this label lest history dub us as ‘the educated barbarians”’. For the militant undergrad, the litmus test of intellectual commitment was which side you were on: the side of imperialism and exploiters or the side of working masses. There was no in-between; no ‘buts’ and ‘howevers’; no reservations and disclaimers; no fence-sitting and no fellow-travelling. You were either on the side of the masses and therefore revolutionary or on the side of imperialism and therefore reactionary. In somewhat convoluted language, the student author tried to capture Baran’s three characteristics of an intellectual. An intellectual as opposed to an intelligent worker is someone who brings to bear on their investigation a historical perspective; sees phenomena as interconnected and not in isolation; is conscious that the part under examination is not the whole truth and that the whole is not simply an aggregate sum of parts but is interconnected in certain relationship to give the whole. An intellectual applies critical reason and is not a prisoner of hegemonic truths. Translated onto the social plane, Baran argued, an intellectual is a social critic. Not only a social critic but a critic whose task, in the language of Marx, is to ‘criticize the existing world ruthlessly … ruthlessly in the sense that we must not be afraid of our own conclusions and equally unafraid of coming into conflict with the prevailing powers’. In the words of Edward Said, an intellectual speaks truth to power, both social and political power. Baran further posited that the traditional formulation of the commitment of the intellectual as an obligation to seek the truth did not take account of the entire problem. ‘For the problem is not merely whether truth is being told but also what constitutes truth in any given case as well as about what it is being told and about what is being withheld’ (Baran 1969: 13). Antonio Gramsci, in his famous Prison Notebooks, takes us beyond Baran and Said in developing the concept of the organic intellectual (Gramsci 1971). Gramsci understood and developed the concept of the intellectual as a social category from the vantage point of the intellectual’s social function. The intellectual performs their social function or carries out their intellectual activity not in isolation but in ‘the ensemble of the system of relations in which these activities (and therefore the intellectual groups who personify them) have their place within the complex of social relations.’ (ibid.: 8) This is the singular most significant point made by Gramsci, which is often overlooked by many observers. Since the social relations of the capitalist society are characterised by social groups and classes involved in the system of production and occupy a particular place in it, so are the intellectuals connected with or related to those social groups. The relationship between the intellectual and their social group in the world of production is not direct or mechanical but rather ‘mediated’ ‘by the whole fabric of society and by the complex of superstructures, of which the intellectuals are, precisely, the “functionaries”’ (ibid.). The whole layers of ideological and cultural superstructures that mediate between the intellectual and the world of production are themselves produced and reproduced by intellectuals in the performance of their social function. The various groups and strata of intellectuals are formed and elaborated not in the abstract but on the concrete terrain of historical processes (ibid.: 11) and, I would add, social struggles. This puts to rest the liberal and radical liberal idea of intellectuals as a social category floating above classes and class struggles. ‘…[O]rganic intellectuals are distinguished less by their profession, which may be any job characteristic of their class, than by their function in directing the ideas and aspirations of the class to which they organically belong’ (ibid.: 3). It is important to underscore that Gramsci’s organic intellectual is rooted in a social class and speaks to the ideas and aspirations of that class. This is unlike Edward Said’s concept of a public intellectual whose constituency is an amorphous public (Said 1994, passim). At the outset it is important therefore to draw a clear distinction between Said’s concept of the public intellectual and Gramsci’s image of the organic intellectual. This brief detour on the idea of the intellectual gives us a handle to flesh out the concept of the Pan-African intellectual. The Pan-African Intellectual What are the essential characteristics of the Pan-African intellectual? First, the Pan-African intellectual is the intellectual of global Africa. Their historical perspective is grounded in the historical trajectory of global Africa. I use the concept of global Africa advisedly. I suggest that this concept helps us to overcome the traditional territorial division between the continent and the diaspora. The concept of global Africa is social, not geographical or territorial. I am arguing that the conceptual world outlook of Pan-Africanism must be located in African people, wherever they may be, regardless of their geographical location/residence or for that matter origins.[2] I am thus suggesting an epistemological shift from geographical to social in our discourse on Pan-Africanism. Second, the Pan-African intellectual must unreservedly acknowledge and take cognisance of the fact that the history of global Africa over the last five centuries is inextricably enmeshed in the history of the capitalist system. The world capitalist system is therefore the broad canvas on which is inscribed the social, political and cultural struggles of the African people. The capitalist system has been inherently racial. Racism is not simply a superstructural phenomenon, as we Marxists often tend to argue, but one of its building blocks. It is in this context that we have to locate both the origins and development of the Pan-African idea and movement. From the first Black Revolution in Haiti in 1791 to Ghana’s independence in 1957, the Pan-African struggle for freedom and liberation has been pitted against various incarnations of capitalism and capitalist imperialism. From Maroon communities established by runaway slaves in the eighteenth and nineteenth centuries to the Land Freedom Army (the so-called Mau Mau) in Kenya or the Maji Maji uprising against German colonialism in what was then called Tanganyika, in the twentieth century, Africans, wielding whatever resources (including cultural) were available to them, have struggled for freedom from capitalist barbarism in the quest to build a humane civilisation. The freedom struggle goes on. Now on track, then derailed, now destroyed, then rebuilt, the Pan-African Freedom Train has never stopped. Slowed it might have been, but not stopped, never. In locating global African struggles within and intimately connected with capitalism, it is inevitable that the Pan-African intellectual should be conversant with and take full but critical cognisance of the most advanced theoretical understanding of capitalism, that is, Marxism. This does not mean and should not mean accepting Marxist dogmas and doctrines, including some of its Eurocentric premises and prejudices. I would go along with Padmore, with some modifications, on the issue of what the Pan-Africanist intellectual’s attitude to Marxism could be. Pan-Africanism recognises much that is true in the Marxist interpretation of history, since it provides a rational explanation for a good deal that would otherwise be unintelligible. But it nevertheless refuses to accept the pretentious claims of doctrinaire Communism, that it alone has the solution to all the complex racial, tribal and socioeconomic problems facing Africa. It also rejects the Communist intolerance of those who do not subscribe to its everchanging party line, even to the point of liquidating them as ‘enemies of the people’ (Padmore 1956: 18-19). The last sentence is derived from Padmore’s own personal experience, when he resigned from the Comintern in 1934 because of Stalin’s pact with France, an imperialist power. Padmore could not stomach Stalin’s revised communist philosophy, that the main enemy of the colonised people was fascism and not imperialist colonial powers. To the explanatory power of Marxism, I would add the central thesis of historical materialism on class struggle, which provides us with a felicitous handle to understand the nature of the state and the underlying motive forces of capitalist social formations. Third, the Pan-African intellectual is a universal intellectual. By this I do not mean the purveyor of West-centric universal values. No. I mean that the commitment of the Pan-African intellectual extends beyond the suffering of their own people to the suffering of other peoples. The Pan-African intellectual is as committed to the struggles of all oppressed and enslaved people. wherever they may be, as to their own people. For the human struggle for freedom is indivisible. To borrow from Edward Said: ‘For the intellectual the task, I believe, is explicitly to universalise the crisis, to give greater human scope to what a particular race or nation suffered, to associate that experience with the sufferings of others’ (Said 1994: 44). This is precisely what some of you, South African comrades, have been doing in the case of the genocidal brutality of Israel against Palestinians. Fourth, the Pan-African intellectual is an organic intellectual. They are or should be the organic intellectual of the working people of global Africa. Here I am proposing another shift, a political shift. This is the shift from the populist language of African people to the socialist language of African working people. It is also a shift from the orthodox Marxist position of the working class (the proletariat) as the agency of revolution to the concept of working people. I believe it is the working people who would carry the next historical task, the task of Pan-African emancipation. How and in what manner the committed Pan-African intellectual becomes an organic intellectual is a practical question to be resolved concretely in specific situations and struggles. However, this does not preclude us from examining what Cabral stated, in the context of national liberation. The petty bourgeois (and he or she is bound to be a petty bourgeois) Pan-African intellectual has a choice: either to serve the compradorial African state opportunistically, using African unity as a prop, or commit suicide as a petty bourgeois and join the working people in their quest for Pan-African emancipation. Finally, the Pan-African intellectual is an irreverent and unapologetic critic of the world as it exists. He or she should subject the concepts, categories, terms and assumptions of the hegemonic bourgeois world outlook and ideology to ruthless scrutiny. He or she must question, interrogate, criticise and expose the parochialisms, prejudices and stories spun by the media of the ruling power, not only political but also social and community power. Do not romanticise ‘our’ culture. Treat it as a terrain of struggle, as Cabral did. The critique should not spare what is taken as common sense, what is incessantly propagated as morality and ethics. Deep under the hegemonic moral sermons lie prejudices and social interests. One of the most important functions of the Pan-African intellectual is to unravel the layers of ideologies and superstructures that mediate between the real-life situation of the people and their consciousness of them. To paraphrase Richard Wright, the committed Pan-African intellectual must draw their strength from the complex consciousness of their people and ‘mould this lore with the concepts that move and direct the forces of history today…’. We must convert people’s scattered Pan-African sentiment into a systematic Pan-African thought. In the same vein, the Pan-African intellectual in the current conjuncture must subject, especially the concept of nation-state and the ideology of nationalism, to a consistent and protracted critique. I believe we are past the nationalist moment. We must fully recognise the historical moment of national liberation and the sacrifices that generations of Africans have made for the liberation of African people from imperialism. Their tremendous efforts to build a nation out of the colonial constructs of ethnic and racial identities left behind by colonialism ought not be brushed aside. I am only saying that we have to and must recognise today’s specific historical conjuncture beyond the nation and its rhetoric and platitudes. Surrendering to unbridled nationalism today would be stoking the flames of xenophobia, racism and ethnicism. Demonising the national project lock, stock and barrel, on the other hand, would be to fail to harness the richness of the national liberation moment to advance the Pan-African project and its emancipatory potential. If yesterday’s freedom fighters become today’s fighters against freedom, we have to call them out. If yesterday’s liberation ideologies become today’s dogmas of state power, we have to expose them. And, of course, if yesterday’s revolutionary intellectuals metamorphose into today’s professional pundits, we have to take issue with them. There is no perpetual truth. All truth is contingent, which comes with its own perils. It is the task of a committed intellectual to discover its contingency and negotiate around its perils. The Pan-African project is a liberation project, not simply a decolonial project. The Pan-African project is an emancipatory project, not simply an epistemological project. It may, perhaps should, engage with both but on its own terms. This brings me to the present historical conjuncture and the tasks ahead. I propose to do this by identifying two historical moments and two concomitant movements, taking the 5th and the 6th Pan-African Congresses as the two major turning points in the Pan-African trajectory. Two Moments, Two Movements The famous 5th Pan-African Congress held in Manchester in 1945 was the turning point in the Pan-African trajectory. Unlike the previous congresses, the 5th Congress had a significant presence of delegates from the continent. George Padmore was the ‘organising spirit’ of the Congress, as Du Bois observed. Padmore succeeded in getting trade union delegations from the Caribbean and the Continent to attend. Briefing Du Bois on the organisation of the Congress, Padmore had lamented that the Pan-African organisations based in England had no mass following. They were elitist organisations. He opined that ‘workers and peasants … must be the driving force behind of any movement which we middle class intellectuals may establish’. Earlier, in February 1945, Padmore had met trade union delegations attending the WFTU Conference and had got them to endorse the Pan-African Congress and a commitment to attend. In a letter briefing Du Bois of the preparations of the Congress, Padmore observed: Today, the African masses, the common people, are awake and are not blindly looking to doctors and lawyers to tell them what to do. This was particularly sharply reflected in the composition of the trade union delegates which came here. They came from the masses and have their roots deep in the masses.[3]<end Q> Padmore’s observation was obliquely a critique of previous Pan-African congresses, which had been essentially an elitist affair. The 5th Congress marked a shift in another respect. The demands of the previous congresses had been pleas to be treated as equal human beings. They revolved around racial discrimination and related matters. The 5th Congress openly came out for independence of African colonies and the demand for self-determination. The Congress thus became the clarion call for national liberation. The Congress resolutions went further, in condemning monopoly capitalism and envisioning some kind of a social democratic future for Africa. And, of course, it paved the way for Pan-Africanism to return home. Kwame Nkrumah and Jomo Kenyatta were the joint secretaries of the Congress. Both were to become the presidents of their respective countries, Ghana and Kenya. Nkrumah continued the Pan-African project after independence, while Kenyatta set out to consolidate a neocolonial proto-bourgeoisie in his country. They symbolised the impending bifurcation in the Pan-African trajectory between state-centred and people-centred Pan-Africanism. The state-centred Pan-Africanism culminated in a call for unity of states. Its apogee was the formation of the OAU, which Nyerere once called a trade union of leaders. The people-centred tendency, which saw Pan-Africanism as a movement and an ideology of struggle for freedom, was pushed to the back burner. The bifurcation was apparent in the two sets of conferences organised by Nkrumah with Padmore’s assistance, after Ghana’s independence in 1957. One was a series of the conferences of independent African states; another was the conferences of the liberation movements, trade unions and other people’s organisations. The most historical of the latter was the All Africa People’s Conference, held in Accra in 1958. The 1958 Conference was attended by, among others, Frantz Fanon, representing the FLN of Algeria, Patrice Lumumba from Congo, Abdulrahman Mohamed Babu from Zanzibar, Tom Mboya from Kenya and Kanyama Chiume from Malawi. With some 300 delegates representing more than 200 million people, the All Africa People’s Conference undoubtedly represented the high point in the Pan-African trajectory. The high ground attained by the 1958 Conference has yet to be reclaimed. The organisers of the 6th Pan-African Congress had hoped to replicate the 1958 Conference. But, as Rodney pointed out, 1974 was not 1958; 1958 was an anticolonial moment whereas 1974 was an anti-neocolonial moment. The contradictions and the visions embodied in the two moments came to a head in the 6th Pan-African Conference held in Dar es Salaam in 1974. If the 5th Congress was the high point in the national liberation movement, then the 6th Congress was the nadir of the Pan-African emancipatory movement. The original initiative to organise the 6th Congress came from radical African-American groups in the United States. The SNCC (Student Non-Violent Coordinating Committee) was the leading organisation. Right from the outset there were differences among the organisers, mainly around two sets of issues: the tension between race and class, and state-centric versus people-centric nationalism. It was agreed that the Congress should be held in Africa. After considering several alternatives, the choice fell on Tanzania. C. L. R. James was involved in drafting the original call. The organisers had agreed that the invitees to the Congress would be non-governmental Pan-African organisations and liberation movements. Once the Tanzania government stepped in, the orientation of the Congress and the list of participants changed from non-state organisations to states. Non-governmental organisations would need an approval of their respective states to attend, thus leaving out many groups, for example in the Caribbean, who were opposed to their governments. This change led many to drop out and boycott the Congress, including C. L. R James. A veteran Guyanese militant and Rodney’s respected elder, Eusi Kwayana, condemned the barring of Caribbean militants and called it ‘the greatest betrayal of Black people in the Caribbean that could have been committed’.[4] A few months earlier, Walter Rodney had circulated his paper for the Congress. It further contributed to many activists boycotting the Congress. It was widely believed that some Caribbean governments had put pressure on Tanzania to the extent that if certain individuals like Rodney attended, they would decline the invitation. In the event, neither James nor Rodney attended the Congress. All Black states and their ruling parties were invited. The Congress was attended by some twenty-eight states, liberation movements and some activists from the US. The opening speech by Nyerere and the two-hour harangue by Sékou Touré became the working documents of the Congress. Rodney’s paper, which he had circulated several months before the Congress, titled ‘Towards the Sixth Pan-African Congress: Aspects of International Class Struggle in Africa, the Caribbean and America’ cast a long shadow over the Congress, albeit in Rodney’s absence. Wole Soyinka was there. He too was instructed not to run his mouth against the Nigerian government. He came away thoroughly disgusted. In my opinion, Rodney’s paper was one of his finest pieces of political writing. He identifies two moments in the trajectory of the petty bourgeoisie: the pre-independence, when the petty bourgeoisie played a progressive role at the head of the masses demanding independence, and the post-independence moment, when the petty bourgeoise in power set to consolidate its power at the expense of the masses, moving Pan-Africanism backstage. Rodney closely analysed the class character of the movement for liberation and the nature and class character of the ruling class after independence. He called this class ‘petty bourgeoisie’. Rodney used the term ‘petty bourgeoisie’ in the same way Fanon alternately used the term ‘middle class’ or ‘national bourgeoisie’ in The Wretched of the Earth. At the time, the term was current in the Marxist debates in Tanzania and elsewhere in East Africa, in which Rodney had participated. Although the debate was moving towards analysing the differentiation of the petty bourgeoisie in power into state bourgeoisie or bureaucratic bourgeoisie, the concepts had not yet become fully integrated in the African Marxist lexicon. Rodney outlined the limits of this proto-bourgeoisie, its incapacity to free the working people from the clutches of capitalism and imperialism on the one hand, and bring about genuine development in the interest of the masses, on the other. He argued that this class was incapable of overcoming the division of the African mini-states ensconced in the colonial borders for that would be against their narrow class interests. The colonial division of the masses in the form of borders had since been sanctified by the OAU, which had become nothing more than a gathering of the bourgeoisies to let off steam. Rodney was not naïve. He fully realised that a Pan-African Conference being held on African soil in the backyard of a petty bourgeois state, however progressive, set serious limits on what could and could not be discussed. He made a number of propositions, which he believed could be the minimum Pan-African platform at the Congress. I summarise a few that I believe still hold true. Rodney argued that the main enemies of the African working people are the capitalist class in the US, Europe and Japan, and that the true liberation of the African people required a struggle against the local allies of international capital on a long road to a socialist future. The ruling compradorial classes were incapable of uniting the continent because that would be against their narrow interests. What was needed, according to Rodney, was to unite progressive groups, organisations and institutions rather than let them be the preserve of the state. In sum, Rodney unambiguously took a class view of the national and international political landscape and believed that the true liberation and emancipation of the working people of global Africa would come through a protracted class struggle. Taking a leaf from Rodney, I would say that the major task of the committed Pan-African intellectual in the present historical conjuncture is to spearhead an insurrection of Pan-African ideas. It is to forge a formidable Pan-African movement bloc by bloc, region by region, continent by continent, a movement that will be truly internationalist and revolutionary, unapologetically anti-imperialist, unambiguously against all parochial ideas and cultural practices that discriminate and divide people along race, colour, ethnicity, gender or sexual orientation. Ultimately, the petty bourgeois Pan-Africanists that most of us are, have to ‘commit’ suicide and be reborn as the organic Pan-African intellectual of the Working People of Global Africa. The struggle is long. The hour is now. So many deeds cry out to be done, And always urgently; The world rolls on, Time presses. Ten thousand years are too long, Seize the day, seize the hour! Mao Tse Tung (1963)[5] Acknowledgements I am grateful to Natasha and Amil Shivji for their indefatigable support and for keeping a watchful eye on never to deviate from one’s principles. Notes [1] The students had been expelled en masse by President Julius Nyerere, visitor to the university because they had opposed the government’s scheme of a mandatory two-year national service. [2] I am aware of the vexed question of who is an African for the purposes of and in the context of Pan-Africanism. This is not the place to go into it. I intend to address it in a different work. [3] Padmore to DuBlois 12/04/1945, Du Bois Papers (MS 312) in University Archives, University of Massachusettes Amherst Libraries http://credo.library.umass.edu/view/full/mums312-b107-i435 [4] Quoted in Wilkins, ‘A Line of Steel’, Location 1695 (Kindle edition). [5] https://www.marxists.org/reference/archive/mao/selected-works/poems/poems34.htm